Self-assembly macroscopic preparation method of low-carbon defective graphene in hot melting state and prepared low-carbon defective graphene
By adjusting the self-assembly time of metal hydroxycarboxylate in the hot melt state, the self-assembly time is adjusted to prepare low-carbon defective graphene, solving the problem of large-scale production in the existing technology, and achieving efficient, environmentally friendly and simple preparation of low-carbon defective graphene.
Patent Information
- Application Number
- CN202510333479.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-07-04
- Estimated Expiration
- 2045-03-20
AI Technical Summary
It is difficult for the existing technology to achieve large-scale production of low-carbon defective graphene, and the existing methods have problems such as high cost, complexity, and unenvironmental protection.
The method of self-assembly of metal hydroxycarboxylate in the hot melt state is adopted to prepare low-carbon defective graphene by adjusting the self-assembly time to form an orderly carbonized structure to reduce defects.
The macro preparation of low-carbon defective graphene is realized, which improves yield and purity, simplifies the process, reduces costs, and is environmentally friendly and suitable for large-scale production.
Smart Images

Figure CN120246998A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new functional materials, and particularly relates to a method for self-assembling and macroscopically preparing low-carbon defective graphene in a hot-melt state, and the prepared low-carbon defective graphene. Background Art
[0002] Since 2004, when Professors Geim and Novoselov from the University of Manchester in the UK successfully isolated graphene through the innovative tape peeling method, this material has become the focus of extensive attention and research hotspot in the academic community due to its unique structural characteristics and excellent properties. The carbon atom connection mode and electronic structure of graphene endow it with excellent physical and chemical properties. Specifically, graphene has an extremely large specific surface area, which provides unlimited possibilities for it in the fields of electrochemistry and materials science; at the same time, its extremely high mechanical strength means that it can withstand various extreme conditions; coupled with excellent thermal conductivity and ultra-high carrier mobility, graphene also shows great application potential in the fields of biomedicine and optics. These excellent properties indicate that graphene may lead a revolution in the field of materials science and open up a new technological era.
[0003] Although the application prospects of graphene materials are broad, the existence of carbon defects in graphene greatly limits its application. Carbon defects will reduce the conductivity of graphene, enhance polarization loss, and significantly affect the electron transport ability. Therefore, the preparation of graphene with low carbon defects is very important for industrial applications. However, the mass production of graphene with low carbon defects faces a series of challenges and limitations. For example, although the mechanical exfoliation method can simply and inexpensively prepare graphene with low carbon defects, its limitation is that it is difficult to accurately control the size of the obtained graphene, and the yield is limited. This method is mainly suitable for small-scale laboratory preparation and is difficult to meet the production requirements of large-scale industrialization. The supercritical fluid exfoliation method provides an efficient way for the preparation of graphene with low carbon defects and can quickly produce graphene. However, during the reaction process, macromolecules such as surface active substances are likely to adhere to the surface of graphene, thus affecting the purity and quality of graphene. In addition, since this method needs to be carried out under high-temperature and high-pressure environments, this brings significant safety hazards and limits its wide application in large-scale production. The preparation of graphene by the oxidation-reduction method can obtain graphene with a relatively complete structure, but the toxic and harmful gases generated during the reaction process will pollute the environment and need to be treated for tail gas. Moreover, the structure and integrity of graphene are often severely damaged by the oxidation of oxidants, resulting in a decrease in the quality of graphene and more structural defects. The chemical vapor deposition method for preparing graphene with low carbon defects can prepare graphene with a complete structure, good quality, and large size, and the number of graphene layers can vary according to conditions such as growth time and growth temperature, with strong controllability, which can promote the large-scale production of graphene. However, its preparation process is relatively complex and the production cost is high, thus limiting the application and popularization of this method.
[0004] In summary, due to factors such as the complexity and low yield of the existing preparation methods of graphene with low carbon defects, it is often difficult to be applied on a large scale. Therefore, how to achieve a preparation method of graphene with low carbon defects that is simple in process, green and environmentally friendly, controllable in conditions, and scalable is worthy of further research. Summary of the Invention
[0005] The purpose of the present invention is to provide a method for macroscopically preparing graphene with low carbon defects by self-assembly in a hot melt state. Using metal hydroxycarboxylate as a carbon source precursor, graphene is prepared by self-assembly in a molten state; by adjusting the self-assembly time in the molten state, the macroscopic self-assembly preparation of graphene with low carbon defects is realized. The preparation method is simple, green and environmentally friendly, controllable in conditions, and scalable for production. Moreover, it can ensure the product quality and greatly improve the purity.
[0006] Another purpose of the present invention is to provide a graphene with low carbon defects, which is prepared by the above method.
[0007] The specific technical solution of the present invention is as follows:
[0008] A method for self-assembling and macroscopically preparing low-carbon defective graphene in a hot-melt state provided by the present invention is specifically as follows: heating a metal hydroxycarboxylate to its melting point and keeping it at a constant temperature under an argon atmosphere, and then heating it to a carbonization temperature. After keeping it at a constant temperature at the carbonization temperature, it is obtained.
[0009] The metal hydroxycarboxylate is selected from sodium citrate, preferably trisodium citrate dihydrate Na3C6H5O7·2H2O;
[0010] The heating to the melting point means heating to the melting point at a heating rate of 1-3 °C / min;
[0011] The heating to the melting point and keeping it at a constant temperature, the constant temperature time is: 0h < constant temperature time < 48h; preferably 12-24h;
[0012] The heating to the carbonization temperature means heating to the carbonization temperature at a heating rate of 5-10 °C / min;
[0013] The carbonization temperature is 500-900 °C;
[0014] The keeping it at a constant temperature at the carbonization temperature, the constant temperature time is 2-8h;
[0015] Further, after carbonization, the obtained material is sufficiently ground to less than 60 mesh, hydrochloric acid is added for washing, filtration by suction, and then washed with water until neutral and dried.
[0016] For the hydrochloric acid washing, the concentration of the hydrochloric acid used is 0.1-0.3 mol / L;
[0017] The drying temperature is 50-100 °C, and the time is 12-24h.
[0018] In the preparation of the present invention, a hydroxycarboxylate containing a monovalent metal ion is used as a carbon source precursor, and low-carbon defective graphene is synthesized macroscopically in one step by self-assembly in a hot-melt state. This process can be divided into a ring-forming reaction, a degreasing reaction, and a polymerization reaction. The hydroxycarboxylate of the monovalent metal ion (trisodium citrate dihydrate) has a special structure of a carboxylate group and a hydroxyl group. After reaching the hot-melt state, the hydroxyl group and the carboxyl group of the hydroxycarboxylate of the monovalent metal ion act as driving forces to promote the rearrangement and assembly of the hydroxycarboxylate. After rearrangement and recombination, an esterification reaction occurs, and NaOH is removed to form a carbon ring containing a lactone group. At the carbonization temperature, the ester group of the carbon ring undergoes a degreasing reaction, the carbon-oxygen bond is broken, and the free half-bonds combine with the half-bonds of the surrounding carbon to form the σ bond of graphene. The bonding mode is sp 2Hybridization initially formed a planar structure. The remaining sodium carboxylate groups underwent an esterification-like reaction with the hydroxyl groups generated by the decarboxylation reaction of the carbon ring. This reaction achieved the polymerization and arrangement of the carbon ring and completed the self-assembly carbonization process. As the assembly time increased, the degree of order in the arrangement of carbon source molecules increased, and the carbon defects on the surface of the synthesized carbon material decreased, thus forming graphene with low surface carbon defects. However, if the assembly time was too long, a decarboxylation reaction would occur, destroying the ordered structure of graphene. Therefore, by regulating the self-assembly process of monovalent metal ion hydroxycarboxylates in the molten state, the one-step mass production of low-carbon defect graphene can be achieved.
[0019] In the present invention, the pre-formed structure formed in the molten self-assembly stage serves as a "template" to guide the ordered arrangement of carbon atoms during the carbonization process and reduce defects. The stepwise temperature increase avoids the violent decomposition of the precursor at a single high temperature, thereby balancing the orderliness and pyrolysis rate. By adjusting the self-assembly time, optimizing the degree of order of the intermediate, and then fixing the structure through carbonization, the mass preparation of low-defect graphene is realized.
[0020] A kind of low-carbon defect graphene provided by the present invention is prepared by the above method. The low-carbon defect graphene is a two-dimensional carbon-based material containing a large amount of sp 2 bonded carbon; it only contains trace carbon defects, and the conduction and valence bands meet at the Dirac point, having significant electronic, optical, and mechanical properties. The g-value intensity of the low-carbon defect graphene prepared by the present invention is less than 0.1, which is a low-carbon defect.
[0021] Compared with the prior art, the present invention firstly prepares a large amount of low-carbon defect graphene in one step by self-assembling monovalent metal ion hydroxycarboxylates in the molten state and adjusting the self-assembly time of the precursor. Compared with the mechanical exfoliation method for preparing graphene, the molten self-assembly method greatly improves the yield of graphene preparation, and the preparation requirements are more convenient; compared with the supercritical fluid exfoliation method for preparing graphene, the purity of the graphene prepared by the molten self-assembly method is greatly improved, there are no macromolecular impurities, and the preparation conditions of the molten self-assembly method are more convenient and easier to achieve mass production; compared with the reduction method for preparing graphene by oxidation, the graphene prepared by the molten self-assembly method has fewer structural defects, is free from the introduction of heteroatoms, and the area of the prepared graphene is also larger, and the conditions for preparing graphene are more convenient; compared with the chemical vapor deposition method, the preparation conditions of the molten self-assembly method are more convenient and mass production can be achieved. In summary, the present invention innovatively realizes the design and preparation of low-carbon defect graphene. The whole operation is simpler and more controllable, the reaction conditions are milder, the controllability and repeatability are better, and the operation process is green and environmentally friendly, and the production cost is low. Description of the Drawings
[0022] Figure 1 SEM image of the graphite carbon prepared in Example 1;
[0023] Figure 2 Raman spectrum of the graphite carbon prepared in Example 1;
[0024] Figure 3 TEM image of the graphite carbon prepared in Example 1;
[0025] Figure 4 SEM image of the graphite carbon prepared in Example 2;
[0026] Figure 5 Raman spectrum of the graphite carbon prepared in Example 2;
[0027] Figure 6 TEM image of the graphite carbon prepared in Example 2;
[0028] Figure 7 SEM image of the graphite carbon prepared in Example 3;
[0029] Figure 8 Raman spectrum of the graphite carbon prepared in Example 3;
[0030] Figure 9 TEM image of the graphite carbon prepared in Example 3;
[0031] Figure 10 SEM image of the graphite carbon prepared in Example 4;
[0032] Figure 11 Raman spectrum of the graphite carbon prepared in Example 4;
[0033] Figure 12 TEM image of the graphite carbon prepared in Example 4;
[0034] Figure 13 EPR images of the graphite carbon prepared in Examples 1, 2, 3 and 4; a is the EPR image of Example 1; b is the EPR image of Example 2; c is the EPR image of Example 3; d is the EPR image of Example 4. Detailed implementation manners
[0035] To make the objectives, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of them. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the scope of protection of the present invention.
[0036] The test materials and reagents used in the following embodiments, unless otherwise specified, can all be obtained through commercial channels.
[0037] For those not specified in the embodiments, the specific technologies or conditions can be carried out according to the technologies or conditions described in the literature in this field or according to the product specifications.
[0038] Example 1 (for comparison)
[0039] A method for macroscopically preparing low-carbon defective graphene by self-assembly in a hot melt state, comprising the following steps:
[0040] a. Heat 5 g of trisodium citrate dihydrate Na3C6H5O7·2H2O to its melting point of 300 °C at a heating rate of 1 °C / min. After self-assembly for 0 h in the hot melt state, then heat it to 700 °C at a heating rate of 5 °C / min and keep it at a constant temperature for 3 h to preliminarily form graphite carbon;
[0041] b. Put the graphite carbon prepared in step a into a mortar and grind it thoroughly to less than 60 mesh, add 0.1 mol / L hydrochloric acid for washing, and then perform further suction filtration and wash it with water until it is neutral. Finally, place the obtained product in a drying oven at 70 °C and dry it for 24 h.
[0042] The SEM characterization of the synthesized graphite carbon is as Figure 1 shown, indicating that the generated carbon material is a two-dimensional sheet structure; as shown by Figure 2 the Raman spectrum, the D peak value is 1345 cm -1 and the G peak value is 1603 cm -1 , and there is no obvious 2D peak, indicating that there is no graphene in the graphite carbon; as shown by Figure 3 the HRTEM of the graphite carbon, the orderliness of the graphite carbon is low. Perform an EPR test: Use the equipment BRUKER EMX PLUS to scan the intensity of the carbon vacancy defects of a 20 mg sample. The vacancy parameters set by the CEL-PF300 series xenon lamp system (a high-light-power full-band light source with a continuous wavelength distribution and a spectral coverage of UV-Vis-IR 200 - 1100 nm) are Center Field 3510.00 G, Sweep Width 100.0 G, Frequency Mon 9.843016 GHz, Power 3.170 mW, Power Atten 10.0 dB, Mod Amp 1.000 G, Mod Freq 100.00 kHz, Sweep Time 60.00 s, Time Const 5.12 ms, and the intensity scan of the carbon defects is achieved. As shown by Figure 13 the EPR shown in a of
[0043] Example 2
[0044] A method for macroscopically preparing low-carbon defect graphene by self-assembly in a hot melt state, comprising the following steps:
[0045] a. Heat 5 g of the precursor sodium citrate dihydrate Na3C6H5O7·2H2O to its melting point of 300 °C at a heating rate of 1 °C / min. After self-assembling for 12 h in the hot melt state, then heat it to 700 °C at a heating rate of 5 °C / min and keep it at a constant temperature for 3 h to preliminarily form graphite carbon;
[0046] b. Put the graphite carbon prepared in step a into a mortar and grind it thoroughly to less than 60 mesh, add 0.1 mol / L hydrochloric acid for washing, and then perform further suction filtration and wash it with water until it is neutral. Finally, place the obtained product in a drying oven at 70 °C and dry it for 24 h.
[0047] The SEM characterization of the synthesized graphite carbon is as Figure 4 shown, indicating that the generated carbon material is two-dimensional; as shown by the Raman spectrum of Figure 5 , the D peak is 1345 cm -1 , the G peak is 1603 cm -1 , and the 2D peak is 2886 cm -1 , indicating that there is a certain amount of graphene in the graphite carbon. Compared with the graphite carbon prepared in Example 1, its 2D peak is significantly increased, indicating the effect of the increased self-assembly time on promoting the assembly of graphene. As shown by the HRTEM of Figure 6 graphite carbon, multiple parallel short lines are graphene microcrystals distributed in different directions, and the arrangement of the carbon material becomes orderly; as can be seen from the EPR shown in b of Figure 13 , compared with the graphene prepared in Example 1, reasonably extending the assembly time is beneficial to reducing carbon defects in the graphite carbon material.
[0048] Example 3
[0049] A method for macroscopically preparing low-carbon defect graphene by self-assembly in a hot melt state, comprising the following steps:
[0050] a. Heat 5 g of the precursor sodium citrate dihydrate Na3C6H5O7·2H2O to its melting point of 300 °C at a heating rate of 1 °C / min. After self-assembling for 24 h in the hot melt state, then heat it to 700 °C at a heating rate of 5 °C / min and keep it at a constant temperature for 3 h to preliminarily form graphite carbon;
[0051] b. Put the graphite carbon prepared in step a into a mortar and grind it thoroughly to less than 60 mesh, add 0.1 mol / L hydrochloric acid for washing, and then perform further suction filtration and wash it with water until it is neutral. Finally, place the obtained product in a drying oven at 70 °C and dry it for 24 h.
[0052] The SEM characterization of the synthesized graphite carbon is asFigure 7 As shown, it indicates that the generated carbon material is two-dimensional; from Figure 8 the Raman spectrum of, the D peak is at 1345 cm -1 , the G peak is at 1603 cm -1 , and the 2D peak is at 2886 cm -1 , indicating that there is a certain amount of graphene in the graphite carbon. However, compared with the intensity of the 2D peak in the Raman spectrum of Example 2, the intensity is greater, indicating a higher content and integrity of graphene. This is because the self-assembly time is extended, and the hydrophilic-hydrophobic push of hydroxyl and carboxyl groups makes the assembly time of the material longer, making the material more ordered. After carbonization, it becomes an ordered graphene material; from Figure 9 as shown by the HRTEM of graphite carbon, multiple parallel short lines are graphene microcrystals distributed in different directions. Compared with Example 1 and Example 2, the material of Example 3 is arranged orderly, forming a graphene material with fewer defects; from Figure 13 as can be seen from the EPR shown in c in, the EPR intensity of the carbon material prepared in Example 3 is low, indicating fewer carbon defects on its surface, proving that a reasonable extension of the assembly time is beneficial to reducing carbon defects on the surface of graphene.
[0053] Example 4 (as a comparison)
[0054] A method for self-assembling and macroscopically preparing low-carbon defect graphene in a hot melt state, comprising the following steps:
[0055] a. Heat 5 g of the sodium citrate dihydrate Na3C6H5O7·2H2O precursor at a heating rate of 1 °C / min to its melting point of 300 °C. After self-assembling for 48 h in the hot melt state, then heat it to 700 °C at a heating rate of 5 °C / min and keep it at a constant temperature for 3 h to initially form graphite carbon;
[0056] b. Put the graphite carbon prepared in step a into a mortar and grind it thoroughly to below 60 mesh, add 0.1 mol / L hydrochloric acid for washing, and then perform further suction filtration and wash it with water until neutral. Finally, place the obtained product in a drying oven at 70 °C for drying for 24 h.
[0057] The SEM characterization of the synthesized graphite carbon is as Figure 10 shown, indicating that the generated carbon material is two-dimensional; from Figure 11 the Raman spectrum of, the D peak is at 1345 cm -1 , the G peak is at 1603 cm -1 , and the 2D peak is at 2886 cm -1 , indicating that there is a certain amount of graphene in the graphite carbon. However, compared with the intensity of the 2D peak in the Raman spectrum of Example 3, the intensity is smaller, indicating that the content of graphene is less than that in Example 3 and the integrity is not high. This is because the self-assembly time is too long, and a decarboxylation reaction will occur during the over-long intermediate assembly, destroying the ordered structure of graphene; from Figure 12As shown by the HRTEM of the graphite carbon, the multiple parallel short lines are graphene microcrystals distributed in different directions. Compared with the material of Example 3, the orderliness of this material is reduced and the surface carbon defects are increased. From Figure 13 As can be seen from the EPR shown in d in
[0058] The descriptions of the above embodiments are for the convenience of those of ordinary skill in the art to understand and use the invention. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative efforts. Therefore, the present invention is not limited to the above embodiments, and the improvements and modifications made by those skilled in the art without departing from the scope of the present invention according to the disclosure of the present invention should be within the protection scope of the present invention.
Claims
1. A method for macroscopically preparing low-carbon defect graphene by self-assembly in a hot melt state, characterized in that, The specific method is as follows: heat the metal hydroxycarboxylate to the melting point under an argon atmosphere and keep it at a constant temperature, and then raise the temperature to the carbonization temperature. After keeping it at a constant temperature at the carbonization temperature, it is obtained.
2. The method according to claim 1, characterized in that, The metal hydroxycarboxylate is selected from sodium citrate.
3. The method according to claim 1, characterized in that Heating to the melting point means raising the temperature to the melting point at a heating rate of 1-3 °C / min.
4. The method according to claim 1 or 3, characterized in that Heating to the melting point and keeping it at a constant temperature, the constant temperature time is: 0 h < constant temperature time < 48 h.
5. The method according to claim 1, characterized in that, Raising the temperature to the carbonization temperature means raising the temperature to the carbonization temperature at a heating rate of 5-10 °C / min.
6. The method according to claim 1 or 5, characterized in that The carbonization temperature is 500-900 °C.
7. The method according to claim 1 or 6, characterized in that Keeping it at a constant temperature at the carbonization temperature, the constant temperature time is 2-8 h.
8. The method according to claim 1, characterized in that, After carbonization, grind the obtained material thoroughly, add hydrochloric acid for washing, filtration by suction, washing and drying.
9. A low-carbon defective graphene prepared by the preparation method according to any one of claims 1-8.
10. The low-carbon defective graphene according to claim 9, characterized in that, The g-value intensity of the low-carbon defective graphene is less than 0.1.
Citation Information
Patent Citations
Method for synthesizing graphite alkene by coordination assembly
CN101618870A
Network-like graphene nanometer material as well as preparation method and application thereof
CN107128902A
Aromatic synthetic graphene self-assembled porous carbon material as well as preparation method and application thereof
CN119218980A
Synthesis method and synthesis apparatus for polyhydroxycarboxylic acid
JP2008001733A
Graphene quantum dots with different types and method for obtaining each of different types of graphene quantum dots
US20160137508A1